Femme/Butch family romances - Harris, Laura A. (Journal of Lesbian Studies, 2002)
My essay theorizes femme/butch family romances against the grain of dominant feminist and lesbian thought that desexualizes the space of mother/daughter desire. I do so through a reading/recoding of the infringing incestuous mommie-boy desires that surface in an archetypal lesbian novel, Jane Rule's Desert of the Heart.
Keywords: approches et analyses; arts; butch; discipline; genre; hétérosexisme; personnes lesbiennes; queer; ressource en ligne; systèmes d'oppressions; études littéraires